Assessment of the Organizational Efficiency in Managing University Sports Championships Based on the Opinions of Sports Activity Staff - ShahbaZ, Zaid Abdul Jabbar (Indonesian Journal Publisher, 2025)
With the growing interest in extracurricular activities within higher education institutions, it has become essential to analyze and assess the efficiency of sports activity departments in organizing university championships. This can be achieved by examining the perspectives of those working in this field, as they are the most qualified to identify the strengths and weaknesses of the organizational system. Organizational efficiency represents a central element in this context. In recent years, noticeable variation has been observed in the levels of an organization from one championship to another, indicating discrepancies in management and planning approaches, as well as in the preparedness of the human resources responsible for sports activities. This prompted the researcher to identify the problem and purpose of the study: to evaluate the level of organizational efficiency in managing university sports championships from the perspective of sports activity staff. The analytical descriptive method was adopted, and the research population was intentionally selected, consisting of sports activity staff at Iraqi universities. The researcher employed a questionnaire as the main tool to study the phenomenon—namely, organizational efficiency. The study concluded that administrative organization and organizational planning received the highest evaluations among the assessed areas, indicating the presence of a solid administrative and structural foundation. The researcher recommended strengthening communication and coordination aspects through the establishment of effective communication channels and scheduling regular meetings between committees.